1990
DOI: 10.1677/joe.0.126r001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Gonadotrophic Effect of Growth Hormone on Oestradiol Production by Human Granulosa Cells in Vitro

Abstract: In-vitro studies in both rodents and man suggest that GH can stimulate ovarian steroidogenesis, but it is not clear whether this effect is mediated by changes in circulating concentrations of insulin-like growth factor-1 (IGF-1) or whether it is a direct action on the ovary (or, indeed, both). In this study the effects of biosynthetic human GH (hGH) on the production of oestradiol and IGF-1 by human granulosa cells in culture were examined using ovarian tissue (from both normal and polycystic ovaries) which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(74 citation statements)
references
References 5 publications
1
69
1
3
Order By: Relevance
“…As higher concentrations of estradiol in pre-ovulatory follicular fluid predict a higher chance of pregnancy [13], GH administration early in the recruitment phase appears to be a better method to be employed in poor responders. Additional stimulating effect of GH on the production of estradiol by granulosa cells has previously been shown [14,15]. Further appropriately designed studies are needed to determine whether effects of GH on follicular fluid estradiol concentration are the only mechanism involved in the improvement of oocyte number and better clinical pregnancy rates in poor responder women or whether other mechanisms also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…As higher concentrations of estradiol in pre-ovulatory follicular fluid predict a higher chance of pregnancy [13], GH administration early in the recruitment phase appears to be a better method to be employed in poor responders. Additional stimulating effect of GH on the production of estradiol by granulosa cells has previously been shown [14,15]. Further appropriately designed studies are needed to determine whether effects of GH on follicular fluid estradiol concentration are the only mechanism involved in the improvement of oocyte number and better clinical pregnancy rates in poor responder women or whether other mechanisms also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I has been shown to serve as an intraovarian regulator of follicle function in rodents, and it exerts direct effects on human and rodent granulosa cell function (31,32). In vitro, IGF-I, in conjunction with gonadotropins, appears to have a role as a promoter of follicle growth (33) and steroid secretion (34,35) and as an antiatretic hormone (36).…”
Section: Discussionmentioning
confidence: 99%
“…7 Growth hormone has shown to increase intra uterine IGF-1 levels. 8 The addition of IGF-1 to gonadotrophins in vitro culture of granulose cells have shown increased gonadotrophin action by several mechanisms like augmentation of aromatase activity, progesterone production, 17 betaestradiol production and luteinizing hormone receptor formation. 9 Several other studies have shown the beneficial effect of growth hormone on poor responders.…”
Section: Discussionmentioning
confidence: 99%